Targeting angiopoietin‐like 3 in atherosclerosis: From bench to bedside. Issue 9 (17th June 2021) - Ling, Ping; Zheng, Xueying; Luo, Sihui; Ge, Junbo; Xu, Suowen; Weng, Jianping
Abstract: Atherosclerotic cardiovascular disease (ASCVD) is the largest cause of morbidity and mortality worldwide. Lipid‐lowering therapies are the current major cornerstone of ASCVD management. Statins, ezetimibe, fibrates and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors effectively reduce the plasma low‐density lipoprotein cholesterol (LDL‐C) level in most individuals at risk of atherosclerosis. Still, some patients (such as those with homozygous familial hypercholesterolaemia), who do not respond to standard therapies, and other patients who cannot take these agents, remain at a high risk of ASCVD. In recent years there has been tremendous progress in understanding the mechanism and efficacy of lipid‐lowering strategies. Apart from the recently approved PCSK9 and ATP citrate lyase inhibitors, angiopoietin‐like 3 (ANGPTL3) is another potential target for the treatment of dyslipidaemia and its clinical sequalae of atherosclerosis. ANGPTL3 is a pivotal modulator of plasma triglycerides (TG), LDL‐C and high‐density lipoprotein cholesterol (HDL‐C) levels, achieved by inhibiting the activities of lipoprotein lipase and endothelial lipase. Familial combined hypolipidaemia is derived from the Angptl3 loss‐of‐function mutations, which leads to low levels of LDL‐C, HDL‐C and TG, and has a 34% decreased risk of ASCVD compared with non‐carriers. To date, monoclonal antibodies (evinacumab) and antisense oligonucleotides against ANGPTL3 have been investigated in clinical trials for dyslipidaemia therapy. Herein, we review the biology and function of ANGPTL3, as well as the latest developments of ANGPTL3‐targeted therapies. We also summarize evidence from basic research to clinical trials, with the aim of providing novel insights into the biological functions of ANGPTL3 and related targeted therapies.